Mathematical modelling of surface irrigation for field crops in Jordan based on soil hydrological-physical properties - Massimi, Mohunnad (Acta Agraria Debreceniensis, 2021)
Jordan suffers from drought and depletion of water resources. In-field crop management, the issue of irrigation scheduling is important and influential. In this research note, a simple method was developed for scheduling surface irrigation of field crops based on inputs of crop ecology, effective root depth, soil texture, soil hydrology, and logical mathematics. It was concluded that the science of mathematics has succeeded to meet academic irrigation scheduling in terms of surface irrigation for field crops based on both soil hydrological and physical traits. Extension scholar has a decision to choose mathematical irrigation model depends on the traditional inputs or updating the model by searching for renewable inputs such as different varieties root depths, optimum row spacing of each crop, drip irrigation mathematical modelling, and digital sensing. In both cases, the input related to the effective root depth is a major and basic factor in mathematical irrigation scheduling. It is, therefore, recommendable that extension research-based systems should focus on basic mathematics to capacitate the complementary role of academics, research, and extension in irrigation modelling, and rural development.